ADVANTAGES OF AIR DUST COLLECTION SYSTEM - Igamberdiyev Anvarjon Uktamovich (European Science Publishing, 2024)
The article presents the results of the operation of a dust collection system for production facilities and an air dust collection system in industrial complexes during the production of gases and atomized or other substances.
Keywords: Dust collection system, air flow, dust filter, container, mechanisms, blower, cleaning devices, cyclone dust collection systems, dust collection device.